You're got to be kidding! : how to keep your job without losing your integrity - DeMars, Nan (John Wiley & Sons, 2011)
In today's super-stressed workplace, an ethical dilemma can come at you when you least expect it. Here's how to do the right thing without losing your integrity or your job. You've GOT To Be Kidding will help you create an ethics-based workplace that's a joy to work in. This isn't the usual top-down, executive-only manual, but an approach to workplace ethics that's as relevant and accessible to employees as it is to managers and executives. From renowned workplace educator and author of You Want Me To Do What?, this book is filled with recognizable examples ripped from today's headlines that put ethical principles in concrete terms. Filled with recognizable examples that put ethical principles in concrete terms. Covers such topics as topics as loyalty, confidentiality, security, office romance, harassment, social networking at work, harassment, workplace bullying, lying for your boss, and even Internet mischief. A practical manual for assessing, discussing, and resolving ethical dilemmas in the workplace With employees at all levels being held more accountable than ever before, You've GOT To Be Kidding gives businesses of all types and sizes a winning set of principles and practices to do business at the highest ethical level and serves as a guide for anyone who wants to do the right thing without losing their integrity or their job."--Publisher's website.